Changes in settlement behavior of Haliotis rufescens larvae after exposure to acidified conditions - Gleason, Molly Sueko (eScholarship, University of California, 2014)
Ocean acidification (OA) could potentially alter the interaction between settling invertebrate larvae and the settlement cue-producing crustose coralline algae (CCA). We hypothesized this arises from the impairment of larval cue detection and/or physiological changes to CCA. We examined the interaction between the larvae of the commercially valuable red abalone (Haliotis rufescens) and its preferred settlement substrata, CCA species Lithothamnium californicum, under high pCO₂ conditions created to mimic future OA scenarios. CCA were exposed to high pCO₂ conditions (treatment pH 0.2 ± 0.05 units lower than ambient) for 6 weeks and larvae were exposed during early development. Physiological studies were first conducted to determine whether high pCO₂ directly impacts CCA growth and larval survival. Three unique orthogonal larval settlement experiments were performed to determine if larval substrate preference was affected by : 1) larval exposure to high pCO₂, 2) CCA exposure to high pCO₂, or 3) both organisms' exposure to high pCO₂. My results show that 1) CCA suffered a reduction in net calcification, 2) four out of five trials did not reveal an impact of high pCO₂ on abalone larval survival, 3) CCA exposure to high pCO₂ did not affect larval settlement to CCA, 4) larval exposure to high pCO₂ reduced settlement to CCA and 5) both organisms exposure to high pCO₂ did not affect settlement. Larval survival and settlement responses were variable after larval exposure to high pCO₂. This may have been a result of the conditions adult abalone were raised, adult fitness and possibly genetic adaptation to OA